2007
DOI: 10.1007/s00262-007-0397-x
|View full text |Cite
|
Sign up to set email alerts
|

The fibronectin attachment protein of bacillus Calmette-Guerin (BCG) mediates antitumor activity

Abstract: FAP is an effective antitumor agent that inhibits tumor growth at a level equivalent to that observed for BCG. This protein may thus provide an alternative to BCG for treatment of superficial bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…6), which appears to favor interactions with the urothelium313233. Finally, binding to fibronectin, described by several authors as being crucial to an efficient treatment343536, was increased when mycobacteria were in the emulsified form, indicating another advantageous character for efficacious attachment.…”
Section: Discussionmentioning
confidence: 93%
“…6), which appears to favor interactions with the urothelium313233. Finally, binding to fibronectin, described by several authors as being crucial to an efficient treatment343536, was increased when mycobacteria were in the emulsified form, indicating another advantageous character for efficacious attachment.…”
Section: Discussionmentioning
confidence: 93%
“…Although γ-irradiation is the least damaging treatment (Fig. 1) and metabolic activity is preserved 14 , the effect of irradiation could modify the physical properties of the mycobacterial surface as the structure of critical fibronectin-binding proteins 22 , affecting their recognition, internalization and trafficking, as well as the export of critical antigens needed to stimulate a proper immune response. Contrary to our results, other authors affirmed that heat-killed BCG or the cell wall skeleton of BCG enhanced the expression of dendritic cell activation markers 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent in vivo studies, showed that intravesically-instilled, radiolabled recombinant FAP was able to bind bladder implanted tumors. Furthermore, intravesical recombinant FAP was capable of eliciting a T cell-dependent antitumor response in immunized mice indicating recombinant FAP, was internalized, processed and presented in context with MHC class I by bladder tumor cells 18 . Since FAP by itself was observed to mediate antitumor activity in FAP-immunized mice 18 , the possibility of using recombinant FAP protein alone as a lower-risk alternative to BCG for therapeutic purposes is currently being explored.…”
Section: Introductionmentioning
confidence: 99%